Spatial Vulnerability Assessment of Extreme Lightning Events in Bangladesh Using GIS - Farukh, MA; Ahmed, SU; Islam, MA; Baten, MA (Journal of Environmental Science and Natural Resources, 2018)
This study explores human death, injury and overall casualties as a result of ongoing extreme lightning events in Bangladesh. Especially the month of May starting from 2010 to mid-2017 were taken under consideration for this study where, a total of 1811 lightning casualties composed of 339 fatalities and 273 injuries are identified. Spatial and geographic aspects of division wise lightning events are evaluated with the help of ArcGIS. The annual average number of fatality is 227 for the whole country whereas, 43 fatalities and 35 injuries over the entire study period was found in May only. The rate of lightning fatality is high in Pirganj of Thakurgaon, Nikli of Kishoreganj, Shibganj of Chapainawabganj, Nawabganj of Dinajpur, Ullapara of Sirajganj, Bagmara of Rajshahi, Bhuapur of Tangail, and Tarail of Kishoreganj. The majority of lightning-related fatalities occurred to males. Maximum people affected by lightning strike during working outside like in field, hoar, road side etc. Farming is the major activity during lightning fatalities. One seventh of death people are affected during stay in indoor like-house, mosque etc. The rural people affected by lightning fatalities accounted 93%. The analysis shows that the highest lightning vulnerable zone is Sunamganj, Sylhet. J. Environ. Sci. & Natural Resources, 10(2): 11-18 2017